Dinamika Kelompok Peternak Kerbau Di Kabupaten Tulang Bawang - Nanda Pardani; Anggun Safitri; Meita Saniyyah Ubay (Prodi Agribisnis, 2025)
Buffalo is one of the livestock that has the potential to be used as a national meat supplier. Currently, there are two buffalo farmer groups supervised by the Tulang Bawang Regency Agriculture Office, namely the Agung Lestari buffalo group and the Jak Gham 1 buffalo group. Buffalo farmer groups need to be developed to improve the welfare of buffalo farmers. The success of a group lies in the dynamism of a group. The purpose of this study is to determine the dynamics of farmer groups and what factors are related to the dynamics of buffalo farmer groups. The research method uses the census method. The study was conducted in Tulang Bawang Regency in January 2025. The population of this study were members of buffalo farmer groups in Tulang Bawang Regency, namely the Agung Lestari Farmer Group located in Penawar Baru Village, Gedung Aji District and the Jak Gham 1 Farmer Group located in Menggala Tengah Village, Menggala District. The sample in this study was all members of the population, totaling 40 buffalo farmers. Data analysis used is descriptive quantitative with rank-spearman analysis. The results of this study indicate that the dynamics of buffalo farmer groups are in the good category. Buffalo farmer groups in Tulang Bawang Regency have been operating dynamically in achieving their goals. Factors related to buffalo farmer group dynamics include the length of time they have been raising buffalo and their motivation. Farmer groups need to pay attention to group dynamics indicators to ensure they successfully achieve their goals. The government and empowerment agencies need to pay attention to group dynamics by considering the farmers' experience in farming and increasing their motivation.